X2+5x-32=2x-4

Simple and best practice solution for X2+5x-32=2x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2+5x-32=2x-4 equation:



X2+5X-32=2X-4
We move all terms to the left:
X2+5X-32-(2X-4)=0
We add all the numbers together, and all the variables
X^2+5X-(2X-4)-32=0
We get rid of parentheses
X^2+5X-2X+4-32=0
We add all the numbers together, and all the variables
X^2+3X-28=0
a = 1; b = 3; c = -28;
Δ = b2-4ac
Δ = 32-4·1·(-28)
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{121}=11$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-11}{2*1}=\frac{-14}{2} =-7 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+11}{2*1}=\frac{8}{2} =4 $

See similar equations:

| -5/6x-1/9x=2 | | (b/7)+(1/4)=19 | | 31+119+x=150 | | -3.4+v/5=-15.9 | | 4(x-6)+4=6x+2(x-6) | | –(7x–2+12)+(-5x–3x+4)=–(-x+7)–(6x–4–7) | | 6(-3)+3y=9 | | 2x2+19x+9=0 | | 2=3x=19/5 | | 2x+7-24=100+4x | | 5(x-2)+6x=7x+4(x-6) | | s/9+26=29 | | –11g=18−20g | | N2/5+2n/6=12 | | (5x-15)+(8x-8)=180 | | 16d=14d+18 | | m/7+40=46 | | 186-w=232 | | 6(9+x)=54 | | 9000m=2700 | | 2x2+x+1=0 | | 5s-4s=17 | | 16=b/7+13 | | 7x–10x=9 | | b+13/4=9 | | -(18-4x)=18 | | 17x=-51;x=-3 | | 85=9d+4 | | 9(k+1)=90 | | 5^n=5^11⋅5^3 | | 4x=4x-4+2x | | 5^n=56^11⋅5^3 |

Equations solver categories